(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Delhi Sultanate is a term comprising five small Delhi dynasties, mostly Turkic or Pastun (Afgan) kingdoms or sultans, who are of Medieval origin in India. Between 1206 1526, the Sultan ruleed from Delhi, when the last Mughal dynasty took office. The subsequent Indo-Muslim cultural merger left monuments in art , music , literature, religion clothing to remain syncretistic. It is assumed that the Urdu language was born in this period as a result of the contact with immigrants speaking Persian and Turkish with Arabic under the Muslim leadership of the local Sanskrit Prairies. The Sultanate of Delhi is only the Indo-Muslim State, which was throned by Rajia Sultana(1236-1240) amongst the few Indian women rulers in 1256.